MAKING AN APPLICATION FOR DETERMINING THE RANKING OF IMMIGRATION POLYTECHNIC STUDENTS WITH THE WEBSITE-BASED PROMETHEE METHOD - Galuh Boy Hertantyo; W Wilonotomo; Dhimas Triand Noviansyah (Polteknik Imigrasi, 2021)
In the process, based on the ranking of the Immigration Polytechnic cadets, the number of considerations objectively indicators or criteria that have been determined. These indicators and criteria have weight values that will be analyzed quickly and structured. So we need a system to help the Immigration Polytechnic make a list of these people or multi-criteria. This study uses the Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) as a Decision Support System (DCS). The PROMETHEE method is one of the groups in the Multi-Criteria Decision Making (MCDM), which will analyze using many indicators or multi-criteria. It will produce output in the form of decision recommendations to its users. In addition, the PROMETHEE method will compare the value of one alternative with another alternative and produce a ranking based on the value that Immigration Polytechnic students get. Researchers conducted two tests by comparing the results of the test data and the results of the system. The tests are accumulated and calculated using the formula for the estimation of the confusion matrix. The final score is 90% which is included in the Excellent Classification and Best Classification.